Examining co-operative challenges in sustaining the economic well-being and education of Muslim reverts (muallaf) in Malaysia - Kamal Basir, Mohd Zuhaili; Zakariah, Muhammad Zulkhairi; Punding, Azlan Yusof; Abdul Razak, Muhammad Anas (Universiti Teknologi MARA Selangor, 2025)
In Malaysia, where religion is intricately linked with state policy, muallaf, individual who convert to Islam, are defined differently under state laws. Islamic teachings emphasise the importance of supporting muallaf by providing them with knowledge, guidance, and financial assistance, particularly through zakat. However, zakat aid is often shortterm and limited by the eligibility criteria for asnaf recipients. To facilitate their integration into Islam and provide sustained support, the establishment of a co-operative for muallaf is proposed. Such cooperatives can offer a broader range of financial services and are more flexible, with greater potential to empower muallaf economically and sustainably. This paper aims to identify the challenges faced by cooperatives in maintaining the financial well-being and educational opportunities of muallaf in Malaysia. This study adopts a qualitative approach. The findings reveal several obstacles encountered by cooperatives in supporting muallaf, including legal limitations, financial constraints, educational barriers, and the limited availability of Islamic products. The study concludes by proposing measures to enhance the economic stability and educational access of muallaf in Malaysia.